Anthropometric and Body Composition Measurements Related to Osteoporosis in Geriatric Population - Sadiye Murat; Bilinç Doğruöz Karatekin; Filiz Demirdağ; Esma Nur Kolbaşı (Medeniyet Medical Journal)
Objective: This study aimed to evaluate different anthropometric and body composition measurements, including weight, body mass index (BMI), body fat percentage (fat%), skeletal muscle index (SMI), a body shape index (ABSI), waist circumference (WC), and hip circumference (HC), in relation to bone mineral density. Methods: This is a cross-sectional study of a total of 482 patients who consulted the geriatric outpatient clinic between 2018 and 2019. Patients were evaluated with dual-energy X-ray absorptiometry. Anthropometric measurements (HC, WC, weight, BMI, and ABSI), as well as body composition analysis (fat% and SMI) by bioimpedance analysis system, were performed. The patients were evaluated with the rapid Assessment of Physical Activity Index in terms of aerobic exercise habits. Results: There was a significant correlation between lumbar spine (LS) T-score and SMI (r=0.36, p=0.000) and between LS T-score and weight (r=0.21, p=0.000), BMI (r=0.10, p=0.045) and WC (r=0.15, p=0.001). There was a statistically significant correlation between femur neck (FN) T-score and fat% (r=0.15, p=0.001), SMI (r=0.15, p=0.010), weight (r=0.22, p=0.000), BMI (r=0.20, p=0.000), WC (r=0.14, p=0.003), and HC (r=0.17, p=0.001). There was no statistically significant correlation between physical activity and LS T-score (n=353, r=0.08, p=0.16) and FN T-score (n=360, r=0.03, p=0.53). In multiple regression analysis, SMI contributes most in predicting FN and LS T-scores. Conclusions: Anthropometric measurements should be carefully selected in the geriatric population. Among the measurements, the strongest relationship was found between LS T-score and SMI.